In a nutshell, a reciprocal transplant experiment reveals local adaptation and fitness trade‐offs in response to urban evolution in an acorn‐dwelling ant. (1st April 2021) - Martin, Ryan A.; Chick, Lacy D.; Garvin, Matthew L.; Diamond, Sarah E.
Abstract: Urban‐driven evolution is widely evident, but whether these changes confer fitness benefits and thus represent adaptive urban evolution is less clear. We performed a multiyear field reciprocal transplant experiment of acorn‐dwelling ants across urban and rural environments. Fitness responses were consistent with local adaptation: we found a survival advantage of the "home" and "local" treatments compared to "away" and "foreign" treatments. Seasonal bias in survival was consistent with evolutionary patterns of gains and losses in thermal tolerance traits across the urbanization gradient. Rural ants in the urban environment were more vulnerable in the summer, putatively due to low heat tolerance, and urban ants in the rural environment were more vulnerable in winter, putatively due to an evolved loss of cold tolerance. The results for fitness via fecundity were also generally consistent with local adaptation, if somewhat more complex. Urban‐origin ants produced more alates in their home versus away environment, and rural‐origin ants had a local advantage in the rural environment. Overall, the magnitude of local adaptation was lower for urban ants in the novel urban environment compared with rural ants adapted to the ancestral rural environment, adding further evidence that species might not keep pace with anthropogenic change.